Optimization of Photoelastic Properties and Stress Relief of Small-Sized Polycarbonate Disks for Granular Material Photoelastic Tests - Hou, M.X.; Tang, M.X.; Hu, H.S. (Проблемы прочности, 2018)
The development of photoelastic tests was strongly enhanced by appearance of polycarbonate, hich turned out to be an excellent photoelastic material. In order to obtain small polycarbonate particles applicable for granular material photoelastic tests, small-diameter transparent cylindrical disks are cut from a polycarbonate plate preliminarily subjected to annealing, in order to provide stress relief. The plate-cutting and annealing regimes are optimized by the comprehensive analysis of mechanical and photoelastic properties of polycarbonate disks of various diameters and constant height of 5 mm. The resulting stress-strain photoelastic visualizations and material fringe patterns are analyzed, in order to verify the effectiveness of the proposed material processing and annealing regimes.